Industrialization, exports and the developmental state in Africa: The case for transformation - Mwangi wa Githinji; Olugbenga Adesida (University of Massachusetts, Department of Economics, 2011)
This essay explores the role of the state in promoting exports and industrialization in the quest for transformation of African economies. It does this by exploring the role of trade in African economies followed by a brief look at the East Asian Developmental state. This is followed by an examination of why many African states have failed at being drivers of transformation. It concludes by examining the potential role of African states in a project of transformation as well as the available avenues and resources for transformation.
Keywords: O1; O2; O3; N17; N47; N57; N67; N77; 330; Africa; economic development; economic history; exports; industrialization; transformation